Грошова модель попиту та пропозиції - Алєксєєв, Д.А. (Математичні машини і системи, 2004)
В моделі пов’язується рівень монетизації економіки України з її ефективністю, тобто зі спроможністю забезпечення попиту населення на товари та послуги. В її побудові на основі диференціальних та різницевих рівнянь використані ідеї вітчизняних вчених: В.С. Михалевича, М.А. Павловського. В модели анализируется связь уровня монетизации экономики Украины с её эффективностью, в частности, с возможностями обеспечения спроса населения на товары и услуги. При построении её на основе системы дифференциальных и разностных уравнений использованы идеи отечественных ученых: В.С. Михалевича, М.А. Павловского. Proposed the model is destined for estimation of the financial position and results of activity of enterprises or companies on the basis of a system of financial indicators. The model is based on a formalized description of a technique that is oriented toward experts engaged in the development of investment projects and actions toward the reorganization of enterprises. The model is supplied with informational support in the form of national statistics of enterprises. Novelty aspects are a two-level system of estimation coefficients and a formalized scheme of computation of financial indicators, which is illustrated by a full-scale example. The scheme includes 34 indicators of qualitative estimation of the financial position of an enterprise.